EFFECT OF VENN DIAGRAM STRATEGY ON SOME DEFENSIVE SKILLS IN HANDBALL FOR STUDENTS - Ammar Hafedh Tuama; Intisar Ahmed Othman; Faisal Ghazi Abdulhasan (European Journal of Humanities and Educational Advancements, 2023)
Through modern and appropriate learning strategies, students can acquire information that benefits m in face of new situations, in changing ideas, issuing judgments, and generating new ideas, and thus y are able to achieve different goals of learning, as y direct energies towards those goals, which y have previously drawn , Which will help to be able and familiar with content of subject, it is a process and that teaching process is based on interaction between educational institution and teacher and student, and therefore specialists and scientists have developed this process, so y created many strategies, methods and teaching methods to communicate information to student clearly and in his simplicity. Many strategies that have contributed to development of educational process from ancient times until modern strategies, which are only development and emergence of old strategies. Venn plan is one of important strategies in education process since ancient times, and it is attributed to its designer John Van in 1880 and is considered one of support strategies that are used to stabilize goals and skills of lesson. research community was chosen in intentional way from second stage students in Faculty of Physical Education and Sports Sciences, Basra University, which numbered (126) students for academic year 2022-2023 AD. Researchers used a handball defense skills tests according to vocabulary of handball curriculum for second stage. Most important recommendations were: 1- Using Venn diagram strategy in teaching various games and events within approach of colleges of physical education and sports science to participate in students in lecture, as well as removing lecture from traditional atmosphere. 2- Conducting many studies and research and topics dealing with modern strategies in teaching